The effective bank supervisor : management skills for improved performance - Jannott, Paul F. (United States of Ameria : Bankers Publishing Company, 1979)
The book covers the basic principles and skills of management. The purpose of this book is to acquaint the first line bank supervisor with the basic concepts of management through a practical, common sense approach.
rua 30/08/16
Loans
Keywords: Bank management; Banks and banking; Personnel Management